Self-inflicted violence: study of the incidence in the first months of the COVID-19 pandemic (Research, Society and Development, 2022)
Self-inflicted violence refers to acts of self-mutilation and suicide attempts in individuals with intense psychological distress. This study is based on the hypothesis that living in the COVID-19 pandemic, by triggering and/or aggravating psychological suffering/illness, predisposes to acts of self-inflicted violence. To test this hypothesis, 493 Compulsory Notification Forms referring to cases of self-inflicted violence in one of the ten health districts in the city of Curitiba were analyzed between the years 2018 to 2020. The data was analyzed based on the evaluation of the association between categorical variables, using the chi-square test or Fisher's exact test (p